Law without justice : why criminal law doesn't give people what they deserve - Robinson, Paul H., 1948- (OUP E-Books., 2006)
This book is a ... for thoughtful legislators and all the rest of us who seek justice for persons charged with crimes-proportional punishment of the guilty, and exculpation of the morally blameless. The authors demonstrate, with remarkable lucidity, how and why the criminal law sometimes deliberately sacrifices justice for other goals, and they provide thoughtful, controversial, and often persuasive suggestions on how we can redesign our legal system to give people their just deserts. [In the book, the authors offer an] account of how the American criminal justice system fails to give offenders their just deserts in a number of different contexts. From the refusal to allow partial exoneration for defenses like mistake of law and insanity to the practical limitations on detecting and prosecuting offenders, [they also] demonstrate through ... discussions of actual cases the many areas where criminal sentencing fails to do justice.-Dust jacket.